Chemical Sensors and Biosensors - Florinel - Gabriel Banica (Wiley-Blackwell, 2012)
This is a modern introductory book on sensors, combining underlying theory with bang up to date topics such as nanotechnology. The text is suitable for graduate students and research scientists with little background in analytical chemistry. It is user-friendly, with an accessible theoretical approach of the basic principles, and references for further reading. The book covers up-to-date advances in the sensor field, e.g. nanotechnology and quantum dots. It includes calculation exercises and solutions, and the accompanying website contains Powerpoint slides